CRM SYSTEMS AS A COMPONENT OF INTERNET MARKETING ENTERPRISES - Ніколаєнко, Ірина; Навроцький, Н.А. (SWorldJournal, 2023)
Highlighting the problem of optimizing business operations in social networks using modern professional, customer - oriented software-CRM systems. The review of scientific research of scientists, both foreign and domestic, is carried out. A number of unre